The introduction of virtual reality in forensic mental healthcare – an interview study on the first impressions of patients and healthcare providers regarding VR in treatment - Kouijzer, M. T. E.; Kip, H.; Kelders, S. M.; Bouman, Y. H. A. (Frontiers in Psychology, 2024)
Background. Recognizing the potential of Virtual Reality (VR) as a powerful technology to support behavior change, the careful introduction of this technology into treatment settings is essential. This is especially important in vulnerable populations like forensic psychiatric patients. This study aims to gain insight from the impressions of both patients and healthcare providers concerning the integration of VR in practice. The study aims to contribute valuable information that guides the introduction of VR technology, ensuring its optimal use in the complex context of forensic mental healthcare. Methods. Semi-structured interviews were conducted with healthcare providers (n=10) working at forensic outpatient clinics and forensic psychiatric patients (n=8). All participants experienced VR before the interview. Inductive thematic analysis was employed for analyzing the interview data. Results. Patients valued the unique opportunity to simulate personal experiences in VR scenarios and reflect on them with healthcare providers. In addition to positive first impressions, areas for improvement were identified, including the wish for enhanced realism and reduced physical discomfort while immersed in VR. Finally, important factors contributing to the successful introduction of VR were identified. For example, taking into account psychological distress experienced by patients or supporting healthcare providers with implementation resources. Conclusion. The integration of VR into forensic mental healthcare holds great potential for behavior change. However, its immersive characteristics also increase the chance of amplifying psychological distress. This emphasizes the need for caution when using VR– especially when a vulnerable patient group is subjected to triggering scenarios. This study advocates for a gradual introduction of the technology and provides valuable insights into essential elements for this introduction in clinical practice. It highlights that even the initial step of integrating VR into practice – the introduction phase – demands careful planning and a personalized approach. This underscores the need for ongoing refinement and a systematic approach to the overall implementation of VR. These efforts are crucial to fully realize its potential in clinical practice.